Enhancing Pencak Silat Education through Application-Based Learning Media: A Comparative Study on Teaching Effectiveness and Student Outcomes - Iwan Saputra; Ade Ros Riza; Eva Faridah; Raswin Raswin; Agung Sunarno (AL-ISHLAH: Jurnal Pendidikan, 2024)
This examination is advancement research that expects to configuration learning media that contains appraisals in hand to hand fighting contests, particularly combative techniques and particularly aiding the field of sports science, particularly in the field of refereeing and sports accomplishments in North Sumatra. An application that contains assessments in both legal and illegal pencak silat competitions is the form of the developed media. These assessments are presented in the form of videos and match scoring. Additionally, the application includes a useful assessment of fundamental martial arts and martial arts techniques for use in classes. This thought emerged when specialists wanted to expect to discover that was more viable and proficient, as well as valuable for selecting contender for combative techniques and hand to hand fighting officials. The distribution of training materials for martial arts referees can also benefit from this application, particularly in the field of refereeing. The information displayed in this study is a correlation of the viability of the learning model for every mark of the evaluation of the new learning model (in the wake of utilizing the application) more successful than the old learning model (prior to utilizing the application). The new learning model has an efficiency of 85.71 percent, while the old learning model has an efficiency of 60 percent. The old learning model's average effectiveness of implementation indicators was 50%, while the new model's average effectiveness was 70%. Therefore, it can be concluded that the new learning model is superior to the old learning model (previous to using a drill machine) after using a drill machine.